CHEMICALLY INITIATED EMULSION POLYMERIZATION OF METHACRYLIC ACID ESTER WITH DIETHYLETHYNYL CARBONATE USING NONIONIC SURFACTANT OP-10 - Ruziev I. Kh.; Oltiboyeva Z. X.; Primova G. J.; Toshpulatova L. Kh. (American Journals Publishing, 2025)
This article discusses the process of chemically initiated emulsion polymerization of methacrylic acid ester with diethylethynyl carbonate in an aqueous medium using the nonionic emulsifier OP-10. The features of the polymerization reaction, the effect of component concentration and synthesis conditions on the stability of the resulting emulsion, particle size and molecular characteristics of the polymer are studied. The data obtained indicate the high efficiency of OP-10 as an emulsifier, providing system homogeneity and latex stability. The results can be used in the development of new polymeric materials with specified physicochemical properties. The regularity of radical chemical initiation of emulsion polymerization of diethylethynylcarbinol methacrylic ether in the presence of APPK, OP-10, OS-10E-30 dispersant was studied.
Keywords: Monomer, initiation, methacrylic acid chloride, heat resistance, triethylamine, gel effect, diethylethynylcarbinol methacrylic ester, emulsifier, emulsion system.